Pengaruh Promosi Jabatan Dan Pelatihan Kerja Terhadap Kinerja Pegawai Dengan Pengembangan Karir Sebagai Variabel Intervening Pada Dinas Sosial Kabupaten Sijunjung - Aisyah Amelia; Ramdani Bayu Putra; Nila Pratiwi; Hasmaynelis Fitri (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
The era of digital technology development has become a trigger for business change, therefore the ability to manage human resources in accordance with current developments is something that is absolutely essential for visionary companies in the digital era. Therefore, the aim of this research is to determine and analyze the influence of job promotions and job training on employee performance through career development at the Sijunjung Regency Social Service. The population and sample for this research were 39 employees of the Sijunjung Regency Social Service. Data collection methods are through surveys and distributing questionnaires. This research model is structural equation modeling (SEM), with analysis tools using SmartPLS 3.0. Based on the research results, it shows that there is a positive and significant influence between Job Promotion and Career Development. There is a negative and significant influence between Job Training and Career Development. There is a positive and significant influence between Position Promotion on Employee Performance. There is a positive and significant influence between Job Training and Employee Performance. There is a negative and insignificant influence between Career Development and Employee Performance. There is a negative and insignificant influence between Position Promotion on Employee Performance and Career Development as an intervening variable. There is a negative and insignificant influence between Job Training on Employee Performance and Career Development as an intervening variable.